Analisis Aksi Jump Serve di Club Bola Voli LavAni dalam Kompetisi Proliga Tahun 2025 - I Gede Bayu Pramana Sandi; Syarif Hidayat; I Wayan Muliarta (SPRINTER: Jurnal Ilmu Olahraga, 2026)
Jakarta LavAni is a professional club that recorded brilliant achievements as the champion of the 2022 and 2023 Proliga. However, in the 2025 Proliga, LavAni had to settle for a runner-up position. Although dominated by experienced players and competent foreign athletes, observations showed inconsistencies in jump serve techniques that often missed the net. This study aims to analyze the effectiveness and technical errors in jump serves performed by the Jakarta LavAni club during competition in the 2025 Proliga. This study used a qualitative descriptive method through match video observation techniques. The sample in this study were 7 videos from: the final four (6 videos), and the grand final (1 video), which were played by Club LavAni in the 2025 Proliga. The research findings showed that Jakarta LavAni's jump serve ability was in the adequate category. Although the basic technique has been mastered, its effectiveness is not optimal. Jump serves are still easily received by opponents due to limitations in jump timing, ball bounce consistency, and power and accuracy of the shot. In general, this technique has been mastered fundamentally but has not reached a lethal level of efficiency. A more structured and sustainable training program is needed, especially on timing and mental stability at critical points, so that the jump serve technique can contribute more points to the team's future success.